Conocimiento materno sobre vacunas y cumplimiento del calendario de vacunación en menores de 1 año Caserío Santa Clara Iquitos 2021 - Sánchez Tapullima, Glenne (2024)
The investigation allowed to determine the relationship between maternal knowledge about vaccines and compliance with the vaccination schedule of children who have reached up to one year of age attended at the IPRESS I-3 Santa Clara de Nanay Iquitos 2021, the approach was quantitative, the design was non-experimental, correlational and the sample was 90 mothers. The interview, the home visit and the documentary analysis were used; the maternal knowledge questionnaire on vaccines had 97.2% validity and 95% reliability, and the checklist for the vaccination record was according to the National Vaccination Scheme of the Ministry of Health of Peru. Low maternal knowledge about vaccines was found with 63.3% and high knowledge with 36.7%. 52.2% did comply with the vaccination scheme according to the corresponding age and 47.8% did not. The Chi-Square results show a significant statistical relationship X2 = 6.377 with p = 0.012. It is concluded that there is a relationship between maternal knowledge about vaccines and compliance with the vaccination schedule in boys/girls from Caserío Santa Clara de Nanay Iquitos.